2008
DOI: 10.1007/s10562-008-9540-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity Relation of Fe2O3–CeO2 Composite Catalysts in CO Oxidation

Abstract: A series of Fe 2 O 3 -CeO 2 composite catalysts were synthesized by coprecipitation and characterized by X-ray diffraction (XRD), BET surface area measurement, Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). Their catalytic activities in CO oxidation were also tested. The Fe 2 O 3 -CeO 2 composites with an Fe molar percentage below 0.3 form solid solutions with the CeO 2 cubic fluorite structure, in which the doped Fe 3+ initially substitutes Ce 4+ in fluorite cubic CeO 2 , but then mostly loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
135
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(158 citation statements)
references
References 44 publications
19
135
2
Order By: Relevance
“…CeO 2 nanoparticles exhibited a strong peak at 462 cm -1 , corresponding to symmetric breathing mode (F 2g ) of oxygen in fluorite structure of CeO 2 (Jha et al 2016 Intensity (a.u.) which is in good correlation with the previous study (Bao et al 2008). ZnO exhibited the bands at 330 cm -1 (E 2 high-E 2 low), 437 cm -1 (E 2 high), and 658 cm -1 (E 2 low ?…”
Section: Raman Analysissupporting
confidence: 93%
“…CeO 2 nanoparticles exhibited a strong peak at 462 cm -1 , corresponding to symmetric breathing mode (F 2g ) of oxygen in fluorite structure of CeO 2 (Jha et al 2016 Intensity (a.u.) which is in good correlation with the previous study (Bao et al 2008). ZnO exhibited the bands at 330 cm -1 (E 2 high-E 2 low), 437 cm -1 (E 2 high), and 658 cm -1 (E 2 low ?…”
Section: Raman Analysissupporting
confidence: 93%
“…In the case of CeO 2 , it has been widely demonstrated that its oxygen mobility abilities can be improved by the modification of its structure through the doping with different cations such as Zr [5], Zn [6], Eu [7], Cu [8], and Fe [9] among others. This enhancement of the oxygen mobility is directly related to the formation of oxygen vacancies, which has been reported as maximum for contents of doping agent around 10 atomic% in Ce-Eu [7], Ce-Fe [10,11] and Ce-Zn [6] systems. The promotion of oxygen vacancies in the modified ceria structures is especially attractive if these materials are employed as catalytic supports.…”
Section: Introductionmentioning
confidence: 79%
“…As presented in recent works, a correct evaluation of the evolution of oxygen vacancies population in pure and doped cerium oxides must be carried out by comparing the area ratio of the oxygen vacancies band and the F 2g signal (Ov/F 2g ) [8,42,43] in order to reduce the possible influence of the particle size and other effects over the shape and intensity of the signals [8,43,46,47]. The Figure 5 inset shows how the population of oxygen vacancies increases with the Zr At.% in our materials.…”
Section: Resultsmentioning
confidence: 99%